ASIMILASI BAGI NARAPIDANA DALAM RANGKA PELAKSANAAN INTEGRASI UNTUK PENCEGAHAN DAN PENANGGULANGAN PENYEBARAN COVID-19PADA BALAI PEMASYARAKATAN KLAS I PADANG - Hendrizal Fira (Jurnal Inovasi Penelitian, 2022)
The purpose of this research in giving of assimilation to prisoners, obstacles faced and efforts by Balai Pemasyarakatan Klas I Padang to solve the obstacles in the giving of assimilation to prisoners in the integration to avoid spreading of covid-19. This research is descriptive research. The approach used is juridical normative and empirical juridic. The data used is secondary and primary. Data collection techniques are library and field. Data analyzed qualitative and served in the descriptive form. The results of this research: the giving of assimilation to prisovers in the in the integration to avoid spreading of covid-19 by through information system of socialiation by website from Directory of General Ministry of Law and Human Right Indonesian Republic by regulation prisoners who 2/3 punishment time until 31st December 2020, child who ½ punishment time until 31st December 2020. Obstacles faced in the giving of assimilation are internal obstacles consist of client limitation in the using of technology information, lack of human resources of socialitation guides and online system that has weakness. Also, external obstacles come from society environment that never receive the prisoners.